SAFEGUARD MEASURES IN THE FRAMEWORK OF ASEAN-KOREA FREE TRADE AGREEMENT (AKFTA) ON TRADE IN GOODS COMPARE TO GATT/WTO - Johan, Eva (Indonesian Journal of International Law, 2015)
Safeguard measures is one of the WTO instruments to protect domestic industry from import product. Safeguards provision has some requirements to fulfill. A safeguard is one of trade instruments regulated on WTO Agreement. The member could provide safeguards measure for protecting his domestic industry in such increased import quantities product and under such conditions as to cause or threaten serious injury to domestic producers. This article aims to compare the rules of safeguard are regulated in Asean-Korea Free Trade Agreement (AKFTA) with WTO Rules. It is concluded that there are some different provisions of safeguard between the two regulations in the aspect of the applicability on the of safeguard measure, the Dispute settlement mechanism and the time period of safeguard measures.